Respostas
respondido por:
1
Resposta:
Explicação passo-a-passo:
Temos a equação x² - 12x + 4 = 0, onde:
a = 1, b = -12 e c = 4
Assim:
Δ = b² - 4ac
Δ = (-12)² - 4.1.4
Δ = 144 - 16
Δ = 128
x = [-b ± √Δ]/2.a
x' = (12 + √128)/2.1
x' = (12 + √2⁶.2)/2
x' = (12 + 2³√2)/2
x' = (12 + 8√2)/2 = 2(6 + 4√2)/2 => x' = 6 + 4√2
x" = (12 - 8√2)/2
x" = 2(6 - 4√2)/2 => x" = 6 - 4√2
S = {x ∈ IR | x = 6 - 4√2 ou x = 6 + 4√2}
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás